Biometric Data Comparison Between Lewis and Sprague Dawley Rats - Steiner, Richard; Dhar, Madhu; Stephenson, Stacy M.; Newby, Steven; Bow, Austin; Pedersen, Alisha; Anderson, David E. (Frontiers in Veterinary Science, 2019)
Introduction: Pressure mapping systems are often used for indirect assessment of kinematic gait parameter differences after repair of critical peripheral nerve defects in small animal models. However, there does not appear to be any literature that studies the differences in normal gait pattern of Sprague Dawley rats compared to Lewis rats using a Tekscan VH4 pressure mat system. The purpose of this study is to assess the gait profile of Lewis and Sprague Dawley rats generated by Tekscan’ s VH4 system to detect similarities and/or differences in gait parameters involving both force and temporal variables. Materials & Methods: The gait profile of 14 Lewis and 14 Sprague Dawley rats was recorded using a Tekscan VH4 pressure map system with two successful walks per animal and gait parameter data was normalized for mean variance between the two rodent strains. Results: The results showed that temporal and normalized force parameters were not significantly different between the two types of rats. Maximum force, contact area, stride length, and adjusted pressure variables were significantly different between the two strains, likely attributed to the body size and weight differential between the strains. Variation in some of these parameters were considered due to differences in overall body size between the two strains, variations in gait kinematics between individual rodent subjects, and the limitations of the current experimental design. Conclusion: For future in vivo models, either Sprague Dawley or Lewis rat strains would be acceptable animal models when comparing base-line gait profiles using the Tekscan VH4 pressure map system when assessing critical defect repairs of peripheral nerves.